Premature Graying of Hair - Bastakoti, Shreya; Upashna, Timothy (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Premature Graying of hair (PGH) is a common and psychologically distressing condition of the hair. It is seen as being aggravated by various triggering factors. But the pathogenesis and the treatment options are still under study and limited. Thus, proper and extensive research seems to be needed.